2019
DOI: 10.1186/s40795-019-0288-5
|View full text |Cite
|
Sign up to set email alerts
|

Diet satisfaction and associated factors among adult surgical orthopaedic inpatients at a teaching hospital in Lusaka province, Zambia; a hospital-based cross-sectional study

Abstract: Background: Poor quality of food services in hospital contributes to low diet satisfaction among inpatients in both developed and developing countries. However, there is paucity of literature on diet satisfaction in health care facilities in the sub-Saharan region and in particular Zambia. Therefore, this study sought to assess levels of diet satisfaction among adult surgical orthopaedic inpatients at a teaching hospital in Lusaka province, Zambia. Methods: A hospital-based cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
7
2
Order By: Relevance
“…In a study by Miyoba N and Ogada I, [16] there was no significant association between variables of age, sex, education level, and overall satisfaction (p > 0.05) with the meal served which is similar to the finding in our study. 64.3% of surgical orthopaedic inpatients in the study were not satisfied with overall quality of hospital meal.…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Miyoba N and Ogada I, [16] there was no significant association between variables of age, sex, education level, and overall satisfaction (p > 0.05) with the meal served which is similar to the finding in our study. 64.3% of surgical orthopaedic inpatients in the study were not satisfied with overall quality of hospital meal.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies have shown no consistent patterns when comparing sociodemographic groups related to satisfaction with hospital foodservice. 2,6,15,16,19,23 In the present study, small but significant differences between groups of patients in terms of sex, age, length of stay and level of food intake were detected. A prolonged hospitalisation seemed to affect the patients' overall satisfaction negatively, and thereby increased the demands on the hospital foodservice.…”
Section: Sexcontrasting
confidence: 38%
“…4,13 Despite studies from foremost Western countries, 13 additional studies from various countries have emerged with more heterogeneous reports of dissatisfaction, mainly attributed to food quality, communication with staff, and physical environment. [15][16][17] Deeper inquiry through qualitative methods has revealed patient satisfaction in the hospital foodservice setting to be complex. The scoping review by Jonsson et al, 14 focused on qualitative studies with patients older than 65 years.…”
Section: Introductionmentioning
confidence: 99%
“…There have been mixed results to date with respect to predictors of patient perceptions of hospital food. Some have suggested patient traits have no effect, [33][34][35][36] whereas others note that gender 23,28,29,37 and age 23,28,29,38,39 are important. Mealtime accessibility challenges, 40 diet type 23,29 and length of stay 23,29,34 also influence perceptions of hospital food.…”
mentioning
confidence: 99%
“…Mealtime accessibility challenges, 40 diet type 23,29 and length of stay 23,29,34 also influence perceptions of hospital food. Because most of these studies were conducted at a single site, 23,28,29,[33][34][35][36]38,39 generalisability is limited. Furthermore, some used unvalidated methods of assessing patients' food quality perceptions.…”
mentioning
confidence: 99%